Mixed-Up Chamelon (The) - Carle, Eric (U. S. A : Harper Trophy Book, 1984)
A bored chamelon wishes it could be more like all the other animals it sees, but soon decides it would rather just be itself.
Keywords: Chamelons-Fiction; Self-acceptance-Fiction